2015
DOI: 10.3390/ijms16059450
|View full text |Cite
|
Sign up to set email alerts
|

A Quantum Chemical and Statistical Study of Cytotoxic Activity of Compounds Isolated from Curcuma zedoaria

Abstract: A series of 21 compounds isolated from Curcuma zedoaria was subjected to cytotoxicity test against MCF7; Ca Ski; PC3 and HT-29 cancer cell lines; and a normal HUVEC cell line. To rationalize the structure–activity relationships of the isolated compounds; a set of electronic; steric and hydrophobic descriptors were calculated using density functional theory (DFT) method. Statistical analyses were carried out using simple and multiple linear regressions (SLR; MLR); principal component analysis (PCA); and hierarc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 35 publications
(39 reference statements)
0
7
0
Order By: Relevance
“…Consequently, compound 3 was elucidated (Fig. 1 The detailed analysis of the NMR data exhibited that 4 was similar to curcumenol 25 with the exception of a hydroxyl linked C-1 in 4 rather than a hydrogen in curcumenol and this deduction was supported by the HMBC and 1 H-1 H COSY data (Fig. 7).…”
Section: Structure Identification Of Isolated Compoundsmentioning
confidence: 81%
“…Consequently, compound 3 was elucidated (Fig. 1 The detailed analysis of the NMR data exhibited that 4 was similar to curcumenol 25 with the exception of a hydroxyl linked C-1 in 4 rather than a hydrogen in curcumenol and this deduction was supported by the HMBC and 1 H-1 H COSY data (Fig. 7).…”
Section: Structure Identification Of Isolated Compoundsmentioning
confidence: 81%
“…The absence of imaginary frequencies confirms that the optimized structures are true minima. The choice of B3LYP was based on previous studies [20][21][22]. The solvent effects were taken into account implicitly by using the PCM, in which, the solute is embedded into a cavity surrounded by solvent described by its dielectric constant [23].…”
Section: Dft Calculationsmentioning
confidence: 99%
“…The other descriptors may be obtained at the DFT level of theory [24] by considering: (i) orbital consideration, which is based on Koopman's theorem where IP = −E HOMO and EA = −E LUMO [25]; (ii) energy consideration, which is based on the use of the classical finite difference approximation, IP = E +1 − E 0 and EA = E 0 − E −1 where E 0 , E −1 , and E +1 are the electronic energies of neutral molecule, when adding and removing an electron to the neutral molecule, respectively [24]; and (iii) internally resolved hardness tensor approach [26][27][28]. Previously, we have reported the structure cytotoxicity activity relationship of 2thiophen-naphtho (benzo)oxazinone derivatives [29] and compounds isolated from Curcuma zedoaria [22] by considering orbital and energy methods in calculating electronic and molecular properties, and the results displayed that both methods give similar results. In another study, De Luca et al tested the three methods to evaluate the solvent effects on the hardness values of a series of neutral and charged molecules, and they concluded that three methods give similar results in the presence of solvent [30].…”
Section: Dft Calculationsmentioning
confidence: 99%
“…Germacrone(19) [20,27] Colorless prisms; melting point: 53-54°C (MeOH). IR (cm À1 ): 1679, 1665, 1445, 1294, 1135.…”
mentioning
confidence: 99%